2015
DOI: 10.1007/s10620-015-3661-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Narrow Band Imaging and Fujinon Intelligent Color Enhancement in Predicting Small Colorectal Polyp Histology

Abstract: The overall accuracy of NBI and FICE was similar for differentiating small polyp histologies during screening colonoscopy. However, better results should be achieved before using NBI or FICE as real-time optical biopsy of colorectal polyps in screening colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…However, FICE had several advantages: clearer images compared to NBI, more practical use, and provision of 10 different polyp images. 5 Kang et al 15 found higher specificity with FICE than with NBI, particularly in the detection of nonpolypoid lesions smaller than 5 mm.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, FICE had several advantages: clearer images compared to NBI, more practical use, and provision of 10 different polyp images. 5 Kang et al 15 found higher specificity with FICE than with NBI, particularly in the detection of nonpolypoid lesions smaller than 5 mm.…”
Section: Discussionmentioning
confidence: 98%
“…Accurate in vivo histologic diagnostic estimations can reduce the complications and costs associated with unnecessary polypectomy. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Three tandem RCTs and one non-tandem RCT have shown no significant benefit of FICE over standard colonoscopy or NBI 55 58 in improving ADR. However, in the tandem RCT by Chung and colleagues, inadequate bowel preparation in at least 50% of cases may have impacted on ADR.…”
Section: Imagingmentioning
confidence: 96%
“…3). Для оценки типа эпителиального образования использо-вали современные классификации S. Kudo и Y. Sano [12,13]. На основании особенностей капиллярного рисунка и структуры поверхности слизистой эпителиальных неопла-зий выставляли предположительный морфологический диагноз и определяли злокачественный потенциал ново-образований.…”
Section: материалы и методыunclassified